The Effect of Litigation Risk on Management Earnings Forecasts* - CAO, ZHIYAN; NARAYANAMOORTHY, GANAPATHI S. (Contemporary Accounting Research, 2011)
We examine the effect of litigation risk on managers' decision to issue earnings forecasts. We use a new ex ante measure of litigation risk, namely, the Directors and Officers liability insurance premium. This choice bypasses significant problems associated with the estimation of ex ante litigation risk in prior studies. By using this measure of litigation risk, our results are more intuitively appealing. We find that when faced with ex ante litigation risk, managers with bad news are more likely to issue an earnings warning. For good news firms, we do not see this effect. We also examine three forecast characteristics: forecast horizon, extent of news revealed and forecast precision. Firms with higher litigation risk tend to issue earnings forecasts earlier if they have bad news but not so when they have good news. They also reveal less news in the forecasts if they have good news. As litigation risk increases, bad news earnings forecasts become more precise. Good news earnings forecasts, however, tend to become less precise relative to bad news forecasts. This differential effect of litigation risk on management earnings forecasts, based on the direction of news, has not been documented by previous studies.